Tests, numerical study and design of Q1100 ultra-high strength steel welded I-section stub columns. (15th October 2022) - Yin, Fei; Yang, Lu; Xu, Kelong; Wang, Jie; Fan, Junwei
Highlights: Experimental tests on Q1100 ultra-high strength steel I-section stub columns. A numerical parametric study considering various cross-sectional geometries. A modified residual stress model with higher accuracy. Current standards assessed via reliability analyses. A new modified direct strength method for the design of Q1100 welded I-sections. Abstract: An experimental and numerical study on the residual stresses and the cross-sectional behavior of Q1100 ultra-high strength steel welded I-sections is reported in this paper. The experimental tests included nine tensile coupons, eight stub column tests and measurements of the residual stresses and geometric imperfections of welded I-section stub columns. Based on the test results, finite element (FE) models were developed and validated, which were then employed in a parametric study to expand the available test data pool. The slenderness limits and design methods for high strength steel stub columns in the European, North American, Australian and Chinese design codes and the DSM method were examined by the test and FE data. Furthermore, a new modified DSM method offering improved accuracy for the design of Q1100 welded I-sections was proposed and validated via reliability analyses.